Desempenho ESG e eficiência do capital intelectual: análise nas empresas brasileiras à luz da teoria dos stakeholders - Ferreira, Douglas da Silva (2023)
With the arrival of the fourth phase of globalization, factors related to the environmental, social and governance imensions of companies, known in the corporate and academic environments as Environmental, Social and Governance (ESG), have been gaining more and more importance in strategic decision-making and operational. ESG performance represents a company's behavior in relation to the environment, society and governance, and may vary according to the company's country, region and sector. Intellectual capital (IC) is considered a strategic asset for organizations that is capable of driving innovation, improving operational efficiency, promoting competitive advantage and increasing perceived value for customers. Thus, in the light of Stakeholder Theory and based on the arguments offered in the literature on ESG and CI performance, this study aims to examine the effect of ESG performance on the intellectual capital of Brazilian companies. The study sample brings together 80 Brazilian companies listed on B3 with ESG performance data available on CSRHub® from 2017 to 2021, totaling 400 observations. For the measurement of ESG performance, data from the CSRHub® was used on a scale from 0 to 100 and for the CI, the VAIC model by Pulic (1998) was adopted. The data were tabulated in an Excel spreadsheet, run in the STATA software with the panel data model and fixed effects. In general terms, the results of the regression analysis indicated a positive and significant relationship between the ESG performance and the intellectual capital of the companies. Thus, considering the studied sample and the analyzed period, it is inferred that by investing in practices oriented to ESG factors, organizations can improve the management of intellectual capital, finding support in the Stakeholder Theory.